1998
DOI: 10.1016/s0002-9270(98)00529-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary hepatic lymphoma in a patient with chronic hepatitis B

Abstract: Primary hepatic lymphoma is a rare disorder and the clinical behavior remains unknown. We report a patient with primary hepatic lymphoma who had chronic hepatitis B. She was asymptomatic; however, a solitary tumor in the left lobe was incidentally detected. After left hepatic lobectomy was performed, a diagnosis of non-Hodgkin's lymphoma was made. No tumor was found except in the liver. Immunohistochemical stains for hepatitis B surface and core antigens were positive in hepatocytes; however, both were negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…On the other hand, a biopsy may reveal a previously unknown lymphoma during the exploration of a solid hepatic mass or after measuring elevated liver enzyme serology [12]. Occasionally, a malignant lymphoma can be detectable in the setting of other liver diseases such as chronic hepatitis B [20, 22], chronic hepatitis C [2, 3, 7, 21, 25], or primary biliary cirrhosis (PBC) [24]. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a biopsy may reveal a previously unknown lymphoma during the exploration of a solid hepatic mass or after measuring elevated liver enzyme serology [12]. Occasionally, a malignant lymphoma can be detectable in the setting of other liver diseases such as chronic hepatitis B [20, 22], chronic hepatitis C [2, 3, 7, 21, 25], or primary biliary cirrhosis (PBC) [24]. …”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppression increases the risk of non‐Hodgkin's lymphoma. There is an association with infections with hepatitis C and hepatitis B viruses 10–12 …”
Section: Discussionmentioning
confidence: 99%
“…Although he was HbsAg negative his viral load was never checked and therefore we can never be certain that he was without disease. Indeed, in the case from Matano et al [9] immunohistochemical staining demonstrated no replicating virus within the neoplastic cellls although they hypothesised that chronic antigenic stimulation by the virus could be associated with the development of lymphoma rather like other immunological conditions such as Hashimotos thyroiditis and Sjogrens syndrome [10] have been linked to the development of extra nodal lymphomas through the local proliferation of lymphoid tissues. Hepatitis B has a strong correlation with hepatocellular carcinoma though no studies have provided a concrete link with lymphoma.…”
Section: Discussionmentioning
confidence: 99%